Exercising in the Fasted State Reduced 24-Hour Energy Intake in Active Male Adults - Jessica L. Bachman; Ronald W. Deitrick; Angela R. Hillman (Journal of Nutrition and Metabolism)
The effect of fasting prior to morning exercise on 24-hour energy intake was examined using a randomized, counterbalanced design. Participants (12 active, white males, 20.8±3.0 years old, VO2max:   59.1±5.7 mL/kg/min) fasted (NoBK) or received breakfast (BK) and then ran for 60 minutes at 60%  VO2max. All food was weighed and measured for 24 hours. Measures of blood glucose and hunger were collected at 5 time points. Respiratory quotient (RQ) was measured during exercise. Generalized linear mixed models and paired sample t-tests examined differences between the conditions. Total 24-hour (BK: 19172±4542 kJ versus NoBK: 15312±4513 kJ; p<0.001) and evening (BK: 12265±4278 kJ versus NoBK: 10833±4065; p=0.039) energy intake and RQ (BK: 0.90±0.03 versus NoBK: 0.86±0.03; p<0.001) were significantly higher in BK than NoBK. Blood glucose was significantly higher in BK than NoBK before exercise (5.2±0.7 versus 4.5±0.6 mmol/L; p=0.025). Hunger was significantly lower for BK than NoBK before exercise, after exercise, and before lunch. Blood glucose and hunger were not associated with energy intake. Fasting before morning exercise decreased 24-hour energy intake and increased fat oxidation during exercise. Completing exercise in the morning in the fasted state may have implications for weight management.